The unwritten rules of managing up : project management techniques from the trenches - Brownlee, Dana (Berrett-Koehler Publishers, 2019)
This book provides insight into the best practices and techniques that project managers have successfully used for decades to manage a wide variety of senior-level stakeholders--ranging from perfectly competent and pleasant to downright dysfunctional and inept. It includes recommendations for managing six particularly challenging--and common--types of senior leaders. Also offers basic techniques to use with any boss, even a great one.